STUDI PENGARUH PERUBAHAN TATAGUNA LAHAN TERHADAP KARAKTERISTIK BANJIR KOTA BIMA - Ismoyojati, Goyu; Sujono, Joko; Jayadi, Rachmad (UI Scholars Hub, 2018)
The high intensity rainfall in December 21st 2016 has caused major flooding in Bima City. It caused infrastructure destructs and considerable losses. The condition of the watershed in the upstream experiencing decrease of forest area and the gorwth of the city were suspected as some of the factors causing the big flood. Significant land-use changing brought impact on the changes of watershed response to rainfall. The purpose of this research was to determine the effect of land use changing on the flood occurence based on the hydrological model of rainfall-flow in Rontu watershed in the City of Bima. In this research, the effect of land use changing was analyzed by determining the value of curve number (CN) of the watershed in 1996, 2006 and 2016. CN was calculated with the help of HEC-GeoHMS 10.3 software. Furthermore, CN value was used in effective rainfall calculation as the input of hydrograph flood simulation by using the Nakayasu synthetic unit hydrograph transform model. The result showed that other than extreme rainfall, the flood was also affected by the land use changing. In Rontu watershed, over the past twenty years (1996 to 2016), land use changing composition occured i e. 28,68% forest decrease, 3,10% settlement increase, 26,83% farm field incease, 5,82% shrubs decrease and 3,62% rice field increase. Such changing in wet conditions in Padolo sub-watershed resulted in increasing CN of 4,55%, peak discharge of 10,26% and runoff volume of 9,82% and in Malayu sub-watershed resulted in increasing CN of 6,78%, peak discharge of 17,29% and runoff volume 18,00%.